Effects of reinforcement delay and rule explicitness on work performance - Kang, Minji; Lee, Kyehoon; Oah, Shezeen (Korean Journal of Industrial and Organizational Psychology, 2013)
This study examined the effects of reinforcement delay and rule explicitness on performance. A 2 (immediate vs. delayed reinforcement) x 2 (explicit vs. implicit rule) factorial design was used. Eighty college students were recruited as participants and were randomly assigned to the four experimental groups. They performed a simulated work task and the dependent variable was the number of the work task correctly completed. Results indicated that in the delayed reinforcement condition, performance for the group who was given an explicit rule was higher than that for the group who was given an implicit rule. In the immediate reinforcement condition, however, performance for both groups was comparable.